Hydrolyzed polyacrylamide biodegradation and mechanism in sequencing batch biofilm reactor. (May 2016) - Yan, Miao; Zhao, Lanmei; Bao, Mutai; Lu, Jinren
Graphical abstract: Highlights: Hydrolyzed polyacrylamide was treated in the sequencing batch biofilm reactor. The differences of key enzyme activities from biofilm and flocs were explored. Proteobacterias, bacteroidetes and planctomycetes were the key microorganisms. Abstract: An investigation was performed to study the performance of a sequencing batch biofilm reactor (SBBR) to treat hydrolyzed polyacrylamides (HPAMs) and to determine the mechanisms of HPAM biodegradation. The mechanisms for the optimized parameters that significantly improved the degradation efficiency of the HPAMs were investigated by a synergistic effect of the co-metabolism in the sludge and the enzyme activities. The HPAM and TOC removal ratio reached 54.69% and 70.14%. A significant decrease in the total nitrogen concentration was measured. The carbon backbone of the HPAMs could be degraded after the separation of the amide group according to the data analysis. The HPLC results indicated that the HPAMs could be converted to polymer fragments without the generation of the acrylamide monomer intermediate. The results from high-throughput sequencing analysis revealed proteobacterias, bacteroidetes and planctomycetes were the key microorganisms involved in the degradation.